Water Damage and Homeowner's Insurance: (1) Insurance Claim - Hyun-Jeong Lee (EDIS)
FCS-3303, a 3-page fact sheet by Hyun-Jeong Lee, describes important things to keep in mind when making an insurance claim for water damage in the home. Includes references. Published by the UF Department of Family Youth and Community Sciences, January 2009.